Investigation of a novel thermochemical heat storage systems for building applications - Mat Wajid, Norhayati (2016)
Heating and cooling account nearly 60% of world total energy consumption and highly depending of conventional energy sources generated by fossils fuels. As the scarcity of oil reserves becomes the jargon issues in all part of the world today, researchers have to look into a robust investigation on finding the alternative energy to alleviate the dependency of conventional energy. Furthermore, if the phenomenon of using fossil fuel remain as the primary energy sources, it would affect adversely on the greenhouse gas emission. In 2008, The Climate Change Act by the UK Government had targeted that 34% cut in 1990 greenhouse gas emissions by 2020 and, at least, an 80% cut in emissions by 2050. Therefore, to achieve this target, more low carbon technology needed to realise the future reduction of emission. Renewable energy technologies such as solar, wind, geothermal and such thought to become the solution to reducing the demand for conventional energy. However, their instability considered as problematic for future energy demand. Thus, a more efficient management of energy demand, coupled with efficient energy storage systems is required. The aim of this study is to develop novel Thermochemical Heat Storage system (THSS) using off-peak power and renewable sources to minimise energy demands from fossil fuels and reducing GHG emissions. Thus, this could be achieved by developed and constructed a unique adsorption heat pipe using a high energy storage density of the nanocomposite Thermochemical material. Other than that, this unique adsorption heat pipe was integrated with a heat-pump circuit for desorption process. In this study, a Novel Thermochemical Heat Storage has been theoretically model, built and tested on a lab scale and a domestic-scale prototype. The chosen Thermochemical Material (Vermiculite + CaCl2) reacting with pure water vapour operates within a closed system. Other than that, result from thermal analysis shown that Vermiculite + CaCl2 could attain higher heat storage capacity of 374 kJ/kg. The heat storage system of this work based on reversible thermochemical reactions, such as adsorption and desorption of composite Thermochemical materials which exhibits very high energy storage density (up to 364 kWh·m3 of material storage). The small scale experimental investigation has found this THSS has the maximum adsorption temperature of 45.07°C to 71.12°C with the corresponding Coefficient of Performance (COP) of 0.53 to 1.34. Another investigation on Solar Heat Solar collector (SHSC) has carried out numerically and experimentally. The numerical study predicted that the temperature lift achieved at 42°C of using 10m2 of the solar collector. Hence, this SHSC has shown the possibility of integrating the TCM (Thermochemical material) with solar thermal energy. Lastly, a domestic scale THSS has revealed that the highest temperature uplift from the adsorption process at 57°C. The economic analysis of a domestic scale THSS has shown that this system will receive payback in 7.5 years with the internal rate of return (IRR) 15.25%. Furthermore, emission analysis demonstrated that this system would reduce 34% of CO2 in 20 years of its lifespans.